Paraneoplastic Neutrophilic Leukocytosis in a Rare Variant of Papillary Thyroid Carcinoma: A Diagnostic Dilemma with Fatal Outcome (Bangladesh Journal of Otorhinolaryngology, 2026)
Background: Papillary thyroid carcinoma (PTC) is the most common thyroid malignancy, typically associated with a favorable prognosis. However, rare histological variants and unusual clinical presentations can pose significant diagnostic challenges. Paraneoplastic neutrophilic leukocytosis is an uncommon manifestation in thyroid malignancy and may mimic infectious or inflammatory conditions, leading to diagnostic confusion.Case Description: We report a case of an adult male patient with an advanced, rare variant of papillary thyroid carcinoma who presented with persistent and marked neutrophilic leukocytosis. Despite extensive evaluation, no evidence of infection or hematologic disorder was identified. Histopathological examination confirmed a rare aggressive variant of PTC. The paraneoplastic leukocytosis was attributed to tumor- related cytokine production. The disease progressed rapidly, culminating in a fatal outcome despite supportive management.Discussion: Paraneoplastic leukocytosis is a rare but important clinical entity in thyroid malignancies, particularly in aggressive variants. It results from tumor secretion of granulocyte colony-stimulating factors and often indicates advanced disease with poor prognosis. Recognition of this paraneoplastic phenomenon is essential to avoid unnecessary antimicrobial therapy and to anticipate rapid disease progression.Conclusion: This case highlights the diagnostic dilemma posed by paraneoplastic neutrophilic leukocytosis in rare variants of papillary thyroid carcinoma. Awareness of this uncommon presentation is crucial for timely diagnosis, appropriate management, and prognostication.Bangladesh J Otorhinolaryngol 2026; 32(1): 45-52